Structural Effects of Nanotubes, Nanowires, and Nanoporous Ti/TiO2 Electrodes on Photoelectrocatalytic Oxidation of 4,4-Oxydianiline - Cardoso, Juliano Carvalho [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Taylor & Francis Inc, 2010)
The present work illustrates the effect of electrolyte composition on the self-organized TiO2 nanotube arrays electrode preparation. The influence of structural and surface morphology of the TiO2 nanotube-like anode on their photoactivity and photoelectrocatalytic performance was also investigated. TiO2 nanotubular array electrodes are grown by anodization of Ti foil in 0.25wt % NH4F/glycerol/water, but nanowires can be obtained in 4% HF-DMSO as supporting electrolyte, even when both are subjected to electrochemical anodization at 30V during 50 h. The morphological characteristics are analyzed by X-ray diffraction (XRD) and field emission scanning electron microscope (FEG-SEM). The electrodes were successfully applied in photoelectrocatalytic oxidation of 4,4'-oxydianiline (ODAN) in aqueous solution, as a model of a harmful pollutant. Complete removal of the aromatic amine was obtained after 3 hours of photoelectrocatalytic treatment on nanotubular arrays electrodes.
Keywords: anodic oxidation; nanoporous electrode; nanowires film; TiO2 nanotubes array